Leveraging on Cloud Technology for Reporting Maternal and Child Health Services at the Community Level in Ghana (Journal of Health Informatics in Africa, 2018)
Background and Purpose: The millennium development goals (MDG) have served as a catalyst in galvanizing governments and ministries to refocus their development agenda to meet set MDG targets. Similarly the Ghana Health Service (GHS) recognizes the importance of an efficient health information system (HIS) for generating quality data for monitoring progress towards achieving set targets of the health related MDGs 4, 5 and 6. This paper is therefore about the GHS effort in using electronic health record system called the e-Tracker to support the provision and reporting of primary healthcare in the area of maternal and child health services at the community level.    Methods: The research approach was case study of selected facilities in one pilot district. Empirical data was collected using qualitative methods such as participant observations, interviews and supplemented by secondary data sources such as training manuals and other official documents. Philosophically the research was informed by interpretive paradigm through subjective meaning for understanding the sociotechnical complexities of implementing the e-Tracker in the health domain. Actor-Network theory (ANT) was considered as an appropriate theoretical lens to conceptualize and investigate the dynamics of introducing a technological artefact into a social system such as the health domain.Results: Findings were that there was realignment of work practices with resultant reflexive effects (positive and negative) on the working environment as a result of introducing information technology artefact into the health domain. And that the sociotechnical effects are emergent and cannot be determined a priori because of the multiplicities in complexity when the social reacts with the technical.     Conclusions: These findings corroborates findings in similar studies in the IS literature in that effects of technological artefacts in complex social-technical system are emergent and cannot be predetermined due to their unpredictability. Furthermore in sociotechnical systems such as the health domain best practice is for the coexistence of electronic and paper systems. Therefore an attempt to completely replace the paper system with the electronic may result in system challenges.Keywords: e-Tracker, Electronic Health Record, Maternal and Child Health